Līlī nasomāṃ pānakhara - Bakṣī, Candrakānta (Navabhārata Sāhitya Mandira, 2009)
Novel based on social themes; previously published in Ravivāranā aṅkamaṃ, a Gujarati newspaper
Novel. - Reprint. Originally published: Amadāvāda : Aśoka Prakāśana, 1984. - Gujarati in Gujarati-Schr
Keywords: Gujarati fiction